0815 Violent Parasomnias In Patients With REM Without Atonia. Parasomnia Overlap Disorder Vs Pure Rem Behavior Disorder. (27th May 2020) - Simmons, J H; Meskill, G J; Lavender, M G
Abstract: Introduction: REM-Behavior-Disorder (RBD) patients are known for parasomnias causing self-injury. On literature review, harm to others using a weapon is not well established. Some opinions state REM-parasomnias do not consist of elaborate actions, such firing a gun. This has significant ramifications in forensic medicine when RBD is a consideration. We reviewed our RBD patients to identify instances in which a gun was used during a parasomnic event to characterize clinical features associated with such behaviors. Methods: We reviewed over 57 RBD cases from Texas, between 2014-2017 seeking parasomnias in which a gun was used. Results: We found two patients in whom a gun was used during a parasomnia, representing < 3.5% of cases. Case-1: 59 y/o F with a 5 year hx of parasomnias of screaming, thrashing, roaming and one instance in which she pointed an unloaded gun at her husband saying she was going to kill him. She had no recollection of the event. NPSG demonstrated REM without atonia, mild OSA (1a AHI of 11/hr) and frequent PLMS. Case-2 presented to a sleep center in 1989 at 33 y/o with 3 year Hx of EDS, found to have mild OSA unresponsive to PAP Tx, then diagnosed with narcolepsy. He later developed cataplexy and progressed to developing parasomnias 15 years later. He demonstrated REM without atonia on a CPAP re-titration NPSG study done in part for his parasomnias, 20 years after original assessment. PLMS were also demonstrated. His parasomnias consisted of yelling, screaming, roaming and one time he woke up finding bullet holes in his closet door with no recollection of firing his gun, which he kept near his bed. Conclusion: RBD is associated with a wide range of parasomnic events, almost never captured in the laboratory. These patients had clear RBD findings. It is possible they had Parasomnia Overlap Disorder in which Non-REM parasomnias occur in patients with RBD. PLMS and or OSA may contribute by fragmenting sleep. Nonetheless, it is clear that RBD patients can have elaborate parasomnias involving the use of weapons. More attention of this is noteworthy since reports are lacking in the literature. Support: N/A